Catastrophic costs and social sequels due to tuberculosis diagnosis and treatment in Brazil - Pedroso, Márcia Regina de Oliveira; Guidoni, Leticia Molino; Zandonade, Eliana; Fregona, Geisa; Negri, Letícya Dos Santos Almeida; Oliveira, Sandra Maria do Valle Leone de; Prado, Thiago Nascimento do; Sales, Carolina Maia Martins; Coimbra, Raisa da Silveira; Galavote, Heletícia Scabelo; Maciel, Ethel Leonor Noia (Epidemiologia e serviços de saúde, 2021)
To evaluate the impact of catastrophic costs on unfavorable tuberculosis treatment outcomes.OBJECTIVETo evaluate the impact of catastrophic costs on unfavorable tuberculosis treatment outcomes.This was a prospective cohort study, conducted in five Brazilian state capitals (Manaus, Recife, Vitória, Campo Grande and Porto Alegre) from June 2016 to July 2018. Logistic regression was used to calculate the odds ratio (OR) and 95% confidence intervals (95%CI).METHODSThis was a prospective cohort study, conducted in five Brazilian state capitals (Manaus, Recife, Vitória, Campo Grande and Porto Alegre) from June 2016 to July 2018. Logistic regression was used to calculate the odds ratio (OR) and 95% confidence intervals (95%CI).Of the 350 participants, 310 were included, of whom 30 presented unfavorable outcomes. Catastrophic cost (OR=2.53 -95% CI 1.13;5.67) and divorce (OR=5.29 -95% CI 1.39;20.05) increased the chances of unfavorable outcomes.RESULTSOf the 350 participants, 310 were included, of whom 30 presented unfavorable outcomes. Catastrophic cost (OR=2.53 -95% CI 1.13;5.67) and divorce (OR=5.29 -95% CI 1.39;20.05) increased the chances of unfavorable outcomes.Financial difficulties during tuberculosis treatment may impair its outcome. Catastrophic cost and divorce were determining factors for treatment outcomes.CONCLUSIONFinancial difficulties during tuberculosis treatment may impair its outcome. Catastrophic cost and divorce were determining factors for treatment outcomes.